Proceedings of the 1st International Conference on Science, Health, Economics, Education and Technology (ICoSHEET 2019) 2020
DOI: 10.2991/ahsr.k.200723.101
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Kegel Exercise for the Acceleration of Perineum Wound Healing on Postpartum Women

Abstract: Postpartum is an important phase because the complication including genetalia infection frequently happen in this phase. perineum wound healing delay is influenced by several factors, such as less nutrients, less of personal hygiene or personal perineum hygiene, less break, less mobilization and exercises as post-partum exercises that could cause infection. The Post-partum Mobilization was applied gradually based on mother's power. One effort to be made to accelerate perineum wound healing was to implement pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
2
0
4
Order By: Relevance
“…Research that has been done related to perineal wound healing is a study conducted by Gustirini (2019) states that kegel gymnastics done in the first week of postpartum is effective for accelerating the healing process of perineal wounds [28]. Another study was also conducted by Nahdiyah (2019) who stated that giving a decoction of red betel leaves for 2 weeks can accelerate the healing of perineal suture wounds [29].…”
Section: B the Effectiveness Of The Hypnoanastesi Methods In Accelera...mentioning
confidence: 99%
“…Research that has been done related to perineal wound healing is a study conducted by Gustirini (2019) states that kegel gymnastics done in the first week of postpartum is effective for accelerating the healing process of perineal wounds [28]. Another study was also conducted by Nahdiyah (2019) who stated that giving a decoction of red betel leaves for 2 weeks can accelerate the healing of perineal suture wounds [29].…”
Section: B the Effectiveness Of The Hypnoanastesi Methods In Accelera...mentioning
confidence: 99%
“…Luka perineum berkaitan dengan tingginya prevalensi masalah kesehatan tertentu yang dapat mempengaruhi kesejahteraan fisik, psikologis dan sosial wanita baik dalam periode segera dan jangka panjang setelah melahirkan 3,5,6 . Masalah kesehatan tersebut antara lain kehilangan darah, disfungsi sistem perkemihan, disfungsi seksual, kelelahan, depresi dan infeksi 3,6 .…”
Section: Pendahuluanunclassified
“…Masalah kesehatan tersebut antara lain kehilangan darah, disfungsi sistem perkemihan, disfungsi seksual, kelelahan, depresi dan infeksi 3,6 . Infeksi nifas dapat disebabkan oleh luka jalan lahir yang tidak mengalami proses penyembuhan dengan baik 5 .…”
Section: Pendahuluanunclassified
“…Many studies have shown that exercise has an important role in the healing of any type of wound. For example, one study reported that exercise promotes oral mucosal wound healing, and another study showed that Kegel exercise in the first week of post-partum accelerated perineum wound healing (38). Exercise is even effective in treating venous leg ulcers (39).…”
Section: The Effects Of Exercise On Wound Healingmentioning
confidence: 99%